Microwave-Assisted Extraction in A Sequential Biorefinery of Alginate and Fucoidan From Brown Alga Sargassum Cristaefolium - Sugiono Sugiono; Mohammad Taufiq Hidayat; Faruk Alrosyidi; Alfan Nur Abadi; Khairul Anam; Sulfiatus Zannuba; Alvin Taufiky; Emrin Hoiriyah; Matheus Nugroho (Universitas Dr Soetomo, 2022)
The brown alga has bioactive alginate and fucoidan, a potential for raw materials the biorefinery industry with core processing of fucoidan and alginate extraction. The research on sequential biorefinery of fucoidan and alginate was conducted in conventional and hydrothermal methods using a smart pressure-cooker, but the yield of fucoidan is low. The improvement was carried out by extracting fucoidan and alginate using microwave-assisted extraction (MAE). This study aimed to obtain the MAE processing conditions that produced the maximum yield of fucoidan and alginate. The factorial design of 2k was used to determine the effect of MAE processing conditions, i.e. temperature, time, and alga/water ratio on fucoidan and alginate yields. The parameters observed were fucoidan and alginate yield. Data analysis and prediction of first-order model and model accuracy was a regression modelling using a design expert program. The result showed that the elevate of temperature MAE processing to 80 oC,for 20 minutes, and alga/water ratio of 2:20 (w/v) increased fucoidan (4.5%) and alginate (40.6%) yield, but it decreased the yield at 100 oC, for 30 minute, and alga/water ratio of 3:30 (w/v). The equation of the first-order model was quadratic, by wich the model test in curvature was found significant at α=0.05. The MAE sequential biorefinery extraction improved fucoidan and alginate yield and had a potential efficiency for commercialization. The maximum response of fucoidan and alginate yield was obtained from a MAE sequential biorefinery at 80 oC,for 20 minutes,and alga/water ratio 2:20 (w/v); further research is needed to optimizing the process.